Efeito Diabetes mellitus gestacional na modulação de genes relacionados ao metabolismo mitocondrial e a implicação na predisposiçao do recém-nascido à obesidade - Silveira, Maruhen Amir Datsch [UNESP] (2015)
Obesity is a multifactorial disease involving complexes interactions between genetic and environmental agents. However, the increased incidence, early onset and severity of this disease, are still not well understood. Several findings have demonstrated that in utero stressors (diabetes, cigarettes, and/or alcohol consumption, etc) can promote genetic and epigenetic changes predisposing to late development of diseases and metabolic disorders, such as obesity. The present study was designed to evaluate the possible relationship between gestational Diabetes mellitus (GDM) and newborn predisposition to obesity his later life. Healthy and GDM pregnant women and their respective newborns were included. Additionally, obese and eutrophic adults were recruted as reference population. Considering the relationship between diabetes and obesity with mitochondrial dysfunction, gene and protein related to mitochondrial metabolism (SOD2 (superoxide dismutase 2), PPARα (peroxisome proliferator-activated receptor alpha) and PPARGC-1β(peroxisome proliferatoractivated receptor gamma coactivador beta) were evaluated in cells from cord and peripheral blood (reference population), and in placenta cells (gene expression profile in maternal and fetal sides). Our results showed an increased gene and protein expression (SOD2, PPARα and PPARGC-1β) in peripheral blood from obese compared to euthrophic subjects (p <0.05). However, the same result was not observed in the placental tissue (gene expression) and in umbilical cord blood cells (gene and protein expression) from GDM women and their respective newborn compared to the non diabetic group, i.e., GDM was not an effective agent to promote transcriptional changes in SOD2, PPARα PPARGC-1β in maternal and fetal sides of placenta, and transcriptional and translational changes in umbilical cord blood cells. In conclusion, SOD2, PPARα and PPARGC-1β gene and protein expression were confirmed as potential ...